Study of the forming limit of 6063 aluminum alloy perforated sheet under in-plane and out-of-plane stretching conditions (Fracture and Structural Integrity, 2025)
The current investigation deals with the forming process of Perforated Sheet Metal (PSM) process. The goal of the work is to determine by experimental and numerical methods the Forming Limit Diagrams (FLDs) of an Al-Mg-Si aluminum alloy.  In order to achieve this objective, Specimens of different widths, obtained by cutting portions from two opposite sides of a circular blank, were used. The FLDs were determined for the two forming tests: MARCINIAK and NAKAZIMA tests. This choice is motivated by the simplicity of the shapes of the blanks and punches used during these tests, but also in order to measure these curves in both flat (MARCINIAK) and curved (NAKAZIMA) zones. A measurement technique using Stereo-Digital Image Correlation (Stereo-DIC) was implemented. For the sake of comparison, the same tests were performed on Non-Perforated Sheet Metal (NPSM). The experimental FLDs were successfully assessed using simulations in Abaqus finite element code. It is namely found that the safe forming region obtained by NAKAZIMA test is higher than that obtained with MARCINIAK test. Furthermore, the maximum tool displacement in NAKAZIMA tests is double that of MARCINIAK tests for all perforated specimens.
Keywords: Stamping; In-plane and out-of-plane stretching; FLD; AA6063; ABAQUS; Stereo-DIC